2021
DOI: 10.3390/applmicrobiol1020013
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Fungal and Bacterial Assemblages in Bulk and Rhizosphere Soils under Solanum tuberosum in Southeastern Wyoming, USA

Abstract: Solanum tuberosum, commonly known as potato, is the most important non-cereal crop in the world. However, its cultivation is prone to disease and other issues. In recent years, a newfound interest in the soil microbiome and the potential benefits it may convey has led researchers to study plant–microbe interactions in great detail and has led to the identification of putative beneficial microbial taxa. In this survey, we examined fungal and bacterial diversity using high-throughput sequencing in soils under a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…1 C). A previous potato microbiome study also reported lower bacterial diversity in rhizosphere soil while slightly higher diversity in the fungal community 25 . Hence, microbiota comparison between bulk and rhizosphere soils could be influenced by complex factors including soil type, climate, agronomy, sampling methods, and crop variety.…”
Section: Resultsmentioning
confidence: 69%
“…1 C). A previous potato microbiome study also reported lower bacterial diversity in rhizosphere soil while slightly higher diversity in the fungal community 25 . Hence, microbiota comparison between bulk and rhizosphere soils could be influenced by complex factors including soil type, climate, agronomy, sampling methods, and crop variety.…”
Section: Resultsmentioning
confidence: 69%
“…The main representatives of the potato core microbiome are Bradyrhizobium, Sphingobium and Microvirga, and the most abundant genera in the rhizosphere are Lentzea and Streptomyces [10,21], which is confirmed by a very recent largescale microbiome study across the US regions [22]. Additionally, Custer et al reported that in the rhizosphere, members of the phyla Actinomycetota and Pseudomonadota showed the highest relative abundances, with Lentzea and Streptomyces being the most abundant genera [23]. Part of the core microbiome is represented by so-called "hub microorganisms" that influence community structure through strong biotic interactions with the host and other microbial species [24].…”
Section: Introductionmentioning
confidence: 83%
“…This is useful because data on childrens’ social relations are difficult to collect directly, but they can often be inferred from bipartite projections. In the biological sciences, the package has been used to examine organism co-occurrences in both plants [ 48 ] and animals [ 49 ], and is used by the package [ 50 ] to extract the backbone of gene-geneset graphs. Beyond these scientific applications, the package has also been used to examine the collaboration relations among the writers, pencilers, and editors responsible for the X-men comic book series [ 51 ], and to recommend holiday movies [ 52 ].…”
Section: Discussionmentioning
confidence: 99%